The prairie dog and its extermination in Kansas - Stafford, J. T. (My University, 1902)
Introduction: It is believed that but one species of prairie-dog (Cynomys Ludovicanus) is found in the state. This genus may be characterized as follows: Size and Form: Length of body about thirteen inches, length of tail about three inches. The tail is covered on the sides and ends with stiff hairs about an inch long which give it a rather bushy appearance. Ears are short and round, laying close to the head, cheek pouches shallow. Feet with five claws, that on the thumb as large as that on the fifth toe. Skull heavily built, the post-orbital processes directed outward. Dentition remarkably heavy; the molar teeth have three transverse grooves on their crowns, first premolar nearly as large as the second. Molar series strongly convergent backward. The color is of a brown on the upper part of the body fading to almost white on the throat and the hinder part of the belly. The eyes are large, dark ad brilliant, with heavy dark lashes. About the nose on the upper lip are long stiff hairs or feelers, similar to those of a cat. The hair on the body is short and stiff. The average dog will weigh about four pounds. The home of the prairie-dog is a burrow in the ground. The excavated earth is piled around the mouth of the burrow so as to form a small mound which is higher than the surrounding ground and in wet weather prevents the water from filling the burrow. The mound also serves as an elevation on which the dog can stand and survey the surrounding country.
Citation: Stafford, J. T. The prairie dog and its extermination in Kansas. Senior thesis, Kansas State Agricultural College, 1902.
Morse Department of Special Collections
Keywords: Kansas; Cnomys ludovicanus; Prairie Dog; Extermination; Eradication; Theses